O papel do grupo e a formação do pensamento autônomo segundo Piaget - Vargas, Claudeonor Antônio de (2016)
This dissertation aims to investigate the role of group work for the formation of autonomous thinking based on the intuitions of the young Piaget. In this sense, we walk the path that leads him to reject the Traditional Education and put himself in defense of the ideals of the emerging New Education movement. This Piagetian rejection of tradition finds its object first in the pedagogical proposition which has its roots at the scholastic philosophy understood as authoritarian and bookish. On the other hand, Piaget is aligned with the active pedagogical perspective of the group work, specifically composed of peer-peers, in relation to which we highlight the main characteristics. We try to demonstrate that, on the basis of this movement towards educational innovation, there is a profound change in the reception of the learners: they cease to be considered passive and are therefore considered as assets. From the core of this receptive transformation to the subjects emerges the concepts of cooperation, solidarity, reciprocity and mutual respect, all revolving around an interactive ideal that occurs between equals. From the conception of the group as a vital element to the development of reason we emphasize its emulatory role to the evolution of consciousness in the levels of the intellect, morality and affection. For a better understanding of Piaget's reasoning, we u nveil the underlying philosophical root of his scientific work. Finally, we reflect on the repercussions of Piaget's profitable relationship with Philosophy, and we abstract some possibilities of renewing of philosophical questions with a view to an idea of Philosophy of Education. We adopted as an investigative methodology the reading and critical analysis of works related to the subject in Piaget and in relevant commentators. We work with the Gadamerian hermeneutic vision that, connected with Piaget's thinking, rejects the concept of measured to human and educational issues and it gives precedence to the concept of adequate. The efforts of reflection lead us to a double conclusion, obviously without the pretense of closing the question. First, we consider that the return to the young Piaget offers a rich alternative to make considerations about educational problems, especially the questions of meaning that pass through the formal educational act in a specific way and the human existence in general. In the second, we believe that in the group work is an expressive potential of human rational formation able to develop the necessary autonomy to the constitution of a singular and collective ethical and existential sense.